The global, the ethnic and the gendered war: women and rape in eastern Democratic Republic of Congo. Issue 4 (2nd April 2016) - Trenholm, Jill; Olsson, Pia; Blomqvist, Martha; Ahlberg, Beth Maina
Abstract : The purpose of this study was to illuminate the perspectives of women who experienced sexual violence perpetrated in the warscapes of eastern Democratic Republic of Congo. Civilians are targeted for rape, loot and pillage yielding deleterious effects on the social fabric and the sustenance the community provides. The article is based on 11 qualitative semistructured interviews and 4 written narratives from women of reproductive age, recruited from organizations providing support post-sexual violation. The study departs from a larger ethnographic project investigating the phenomenon of war-rape. Thematic analysis guided the analysis through the theoretical lenses of structural violence and intersectionality. The women expressed total insecurity and a multitude of losses from bodily integrity, health, loss of family, life course possibilities, livelihoods and a sense of place; a profound dispossession of identity and marginalization. Pregnancies resulting from rape reinforced stigma and burdened the survivor with raising a stigmatized child on the margins of society. Perpetrators of rape were mostly identified as Interhamwe (Rwandan Hutus rebels) who entered Congo after the Rwandan genocide in 1994. Their goal, according to the women, was to spread HIV and impregnate Congolese women, thereby destroying families, communities and society. The women survivors of war-rape described experiences of profound loss in this conflict which has global, ethnic and gendered dimensions. Congo's conflict thus requires critical reflection on how local wars and subsequent human suffering are situated in a matrix of globalization processes, enabled by transnational actors and embedded in structural violence.